Atrioventricular septal defect and tetralogy of Fallot - A single tertiary center experience: A retrospective review - Khaled A Alhawri; Colin J Mcmahon; Mohammed M Alrih; Yamin Alzein; Asad A Khan; Suhaib K Mohammed; Khaled S Alalwi; Kevin P Walsh; Damien P Kenny; Jonathon G McGuinness; Lars Nolke; John M Redmond (Wolters Kluwer Medknow Publications, 2019)
Background: Complete atrioventricular septal defect (CAVSD) in association with tetralogy of Fallot is a rare and complex disease that makes its repair more difficult than repair of either lesion alone. We reviewed retrospectively our experience in managing this lesion. Patients and Methods: Between February 2006 and May 2017, 16 patients who underwent repair of CAVSD/tetralogy of Fallot (TOF) were reviewed retrospectively. Fifteen patients had trisomy 21. Five patients underwent primary repair while eleven patients went for staged repair in the form of right ventricular outflow tract (RVOT) stenting (n = 9) or systemic to pulmonary (S-P) surgical shunt (n = 2). RVOT stenting has replaced surgical shunt since 2012 in our center. Early presentation with cyanosis was the main determinant factor for staged versus primary repair. Results: The median age at first palliation was 46 days (range 15-99 days). The median age at total repair for both groups was 6 months (range 3-18 months); the median age for the palliated patients was 6.5 months (range 5-18 months) while the median age for primary repaired patients was 5 months (range 3-11 months). The median weight at final repair was 6.9 kg (3.7-8.2 kg). The pulmonary valve was preserved in five patients (31%), four of them had no prior palliation. Chylothorax occurred in 50% of the patients. One late mortality occurred after final repair due to sepsis. Conclusion: CAVSD/TOF can be repaired with low mortality and morbidity. The use of RVOT stent has replaced the surgical (S-P) shunt with acceptable results in our center.